Dynamic Tensile Deformation of High Strength Aluminum Alloys Processed Following Novel Thermomechanical Treatment Strategies. Issue 8 (21st August 2020) - Scharifi, Emad; Sajadifar, Seyed Vahid; Moeini, Ghazal; Weidig, Ursula; Böhm, Stefan; Niendorf, Thomas; Steinhoff, Kurt
Abstract : Interesting effects on the microstructural evolution and dynamic tensile deformation behavior of aluminum alloys AA6082 and AA7075 are revealed by investigating the influence of cooling rates within a novel thermo‐mechanical process. Dynamic tensile tests at strain rates of 40 to 400 s −1 coupled with digital image correlation show an increase in yield strength, ultimate tensile strength, but also in elongation to failure with increasing strain rate. Further details can be found in the article number 2000193 by Emad Scharifi and co‐workers.